The impact of farmers’ digital literacy on farmers’ enthusiasm for grain cultivation: Findings from the “Double Hundred and Thousand” farmers in Jiangxi province - Zhipeng Wang; Yuqin Song; Huiping Xie; Chaoqun Li; Yujie Hu; Zhihua Wu; Jianghua Chen (PLoS ONE, 2025)
Enhancing farmers’ enthusiasm for grain cultivation is crucial for ensuring national food security. Based on survey data from the “Double Hundred and Double Thousand” farmers in Jiangxi Province, this study measures farmers’ enthusiasm for grain cultivation through their double-cropping rice cultivation behavior and employs Probit and Tobit models to empirically analyze the impact of farmers’ digital literacy on their enthusiasm for grain cultivation in traditional double-cropping rice production areas of Jiangxi, as well as its underlying mechanisms. The findings reveal: (1) Improving farmers’ digital literacy exerts a significantly positive influence on their enthusiasm for grain cultivation, promoting double-cropping rice adoption and expanding cultivation areas in traditional production regions. This conclusion remains robust after rigorous testing. (2) Mechanism analysis identifies three pathways: accelerating farmland transfer-in, facilitating the utilization of agricultural machinery socialization services, and promoting the adoption of green grain production technologies, through which enhanced digital literacy drives double-cropping rice cultivation and elevates cultivation enthusiasm. (3) Heterogeneity analysis demonstrates that the positive effect of digital literacy on double-cropping rice cultivation is more pronounced among farmers with higher educational attainment and the level of household part-time farming. Therefore, policies should prioritize elevating farmers’ overall digital literacy, narrowing digital capability gaps, refining land transfer procedures and mechanisms, leveraging the advantages of farmers’ cooperatives, and advancing the dissemination of agricultural machinery socialization services and green grain production technologies.